Ekspresi Gambar Anak dalam Respresentasi Deviasi Perilaku Diri - Dwi Nur Hidayah; Nur Fajrie; Sucipto Sucipto (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2020)
The purpose of this research is to analysis the work of illustrated images in representing deviation of self behaviour’s elementary school students. This research method is qualitative with a case study approach chosen as a study participant of 3 students. The Data collection techniques used are in-depth interviews, documentation, observation. Analysis of the validity of the data used in this study is use triangulation and then analyze the data by reducing data, presenting data and verifying. The results obtained are image expressions of thoughts, ideas, and self-concepts regarding the cause of the deviation of expression symbols in the visualization of student images. Keywords: Expression, child image, behavior deviation, elementary school